1982
DOI: 10.1192/bjp.140.3.280
|View full text |Cite
|
Sign up to set email alerts
|

Once Weekly Pimozide versus Fluphenazine Decanoate as Maintenance Therapy in Chronic Schizophrenia

Abstract: In a double blind trial, 28 male chronic schizophrenic in-patients received either pimozide, given once weekly, or fluphenazine decanoate, given mostly once fortnightly. There was no difference in relapse rates over nine months. However, three-quarters of the patients on pimozide who completed the trial developed at least mild tardive dyskinesia. All patients on pimozide lost weight, the average loss being 5.4 kg (12 lbs). Plasma pimozide levels suggested satisfactory drug compliance. Plasma prolactin levels c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Randomized-controlled trials (RCTs) have shown few therapeutic differences between conventional antipsychotics in oral and long-acting injectable formulations (Levine et al, 1980;McCreadie et al, 1982). A systematic review of RCTs found that depot typical antipsychotics conferred a benefit over oral antipsychotics in terms of an overall improvement, but there were no differences in relapse rates, study discontinuation or adverse effects (Adams et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Randomized-controlled trials (RCTs) have shown few therapeutic differences between conventional antipsychotics in oral and long-acting injectable formulations (Levine et al, 1980;McCreadie et al, 1982). A systematic review of RCTs found that depot typical antipsychotics conferred a benefit over oral antipsychotics in terms of an overall improvement, but there were no differences in relapse rates, study discontinuation or adverse effects (Adams et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The question in particular then is how better to deliver antipsychotics at the lowest possible, whereby dose and interval are relevant. Further novel strategies may be considered and should be learnt from the past such as innovative once weekly pimozide administration (McCreadie et al, 1982). With the fact in mind that poor adherence to (or withdrawal from) antipsychotic medications, for which adverse effects may be a cause, is an established risk factor for relapse, further investigations are certainly indicated to explore more user friendly manner of pharmacotherapy for clients with schizophrenia.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…Extended but regular dosing strategies or drug holidays have been studied in the past (e.g. 4 day per week or weekly administration of pimozide (McCreadie et al ., ; McCreadie et al ., )), and more work on dosing interval is necessary especially from the viewpoint of long‐term relapse prevention.…”
Section: Optimal Dose and Dose Interval Of Maintenance Antipsychoticsmentioning
confidence: 99%
“…Given on 4 days a week, McCreadie et al (1980) found that it was as effective in maintenance as depot fluphenazine. In an intriguing study, it was then given once weekly to a group of in-patients using the same comparator (McCreadie 1982). On the basis of prior treatment regimes, doses ranged from 10 to 60 mg pimozide once weekly.…”
Section: Diphenylbutylpiperidinesmentioning
confidence: 99%